PENGARUH MODULUS HALUS BUTIR PASIR LAUT TERHADAP KUAT TEKAN BETON (Tinjauan Penggunaan Pasir laut di Kota Bengkulu) - Fepy Supriani (Inersia: Jurnal Teknik Sipil, 2019)
The availability of the sand in the coastal regions enable the society nearby to use it directly as one of the material of the concrete building. The coastal fine sand with round surface, and uniform grading will reduce the interlocking among the granules. The sand of each region on the coast of Bengkulu visually have different characteristics, also if compared with river sand and mined sand, especially the fineness of the grain. The level of the grain fineness can be seenfrom the grain fineness modulus. This study aims to find out the use of the coastal sand of different fineness to the strength of concrete, as well as the effect of concrete curing by using sea water and fresh water to the strength of the concrete. The coastal sand used in this study was taken from North Bengkulu areas namely Lakok beach, Sentolong beach and Air Padang beach. Each of the sands visually are different in color and grain size. As the comparator, river sand and mined sand are used. The designed samples are concrete cube with dimensions of 15 cm, water to cement ratio of 0.5 and 50-120 mm slump. The test was conducted at 28, 56 and 90 days of the concrete ages. The results showed that the usage of the sand in concretematerials can provide a positive outcome for the coastal sand with coarse gradations and modulus of grains. The usage of Lakok beach sand in concrete test results show that for any age of the concrete samples, the concrete compressive strength are the highest, even exceeds the compressive strength of the concrete using river sand and mined sand. Air Padang beach sand has the finest gradation and produces concrete samples with the lowest compressive strength. The concrete cured by submersion in sea water has lower compressive strength of the concrete compared to the concrete cured by submersion in fresh water.